Business ethics, illegal trade practices and rise of e-commerce industry - Lina Maulidiana, Idham, Tulus Suryanto, (Opción, 2019)
This study examined the new laws related to online business inIndonesia and the extent of freedom given to foreign investors. It alsodiscusses whether new regulations would be able to check illegal tradepractices. Using a survey methodology the study identified a few issuesrelated to e-commerce transaction in Indonesia. Findings reveal that theIndonesian online business is growing but at the cost of compromiseswith legal mechanisms. In conclusion, the current study has assessedthe need and importance of a legal mechanism to exist within thedomestic Indonesian law to prevent unethical practices in ecommercetransactions.